ISOLASI DAN IDENTIFIKASI EUGENOL DARI MINYAK LAWANG (CINNAMOMUM CULLILAWAN, BL) - Gugule, Sanusi (Sainstek, 2007)
Eugenol has been isolated and identified from oil of lawang (Cinnamomum cullilawan, BL). Before conducting isolation lawang oil was characterized. The eugenol was separated from the oil by fractional distillation under reduced pressure. The purities of all products were tested with gas liquid chromatography and determination of physical constants, such as refractive index and density. The structures were identified with infrared spectrophotometry, 1H nuclear magnetic resonance spectrometry, and mass spectrometry. The experimental result showed that the percentage yield of eugenol obtained from oil of lawang was 25,51 %.